Abatacept versus tocilizumab for the treatment of rheumatoid arthritis in TNF inhibitor inadequate responders: study protocol of the SUNSTAR randomised controlled open-label superiority trial - Bruno Fautrel; Pascal Richette; Christian Roux; Grégoire Cormier; Martin Soubrier; Xavier Mariette; Christophe Richez; Jacques-Eric Gottenberg; Hubert Marotte; Jacques Morel; Rene-Marc Flipo; Jerome Avouac; et al. (BMJ Open)
Introduction Biological disease modifying antirheumatic drugs (bDMARDs) have a central role in the treatment of rheumatoid arthritis (RA). Tumour necrosis factor inhibitors (TNFis) are commonly used as first-line agents, while non-TNFis (tocilizumab, abatacept and rituximab) have shown to be non-inferior to TNFis in head-to-head trials. In case of TNFi inadequate response, using other mechanisms of action provides a better response than using an alternate TNFi. Which non-TNFi bDMARD administered subcutaneously to allow for ambulatory management to choose in case of first line TNFi inadequate response has not been tested in a randomised clinical trial, while observational data support a potential superiority of tocilizumab over abatacept.Methods and analysis The SUNSTAR (SUbcutaNeouS Tocilizumab vs Abatacept in TNF Alpha inadequate responders for the treatment of Rheumatoid arthritis) study is a 52-week prospective, randomised, multicentre, open-label, superiority phase IV trial comparing subcutaneous tocilizumab with abatacept in a 1:1 ratio. Patients with active RA (Disease Activity Score-erythrocyte sedimentation rate >3.2 and Clinical Disease Activity Index (CDAI) >10) and with inadequate 3-month response to a first or second TNFi are included in 25 centres in France. The primary outcome is the CDAI improvement at week 24. Intention-to-treat analysis will be applied primarily. The secondary outcome is a composite outcome of the percentage of responders defined as a CDAI<10, no use of rescue treatment after week 12 and no experimental treatment change, at weeks 12, 24 and 52.Ethics and dissemination Ethics approval was obtained from the committee for the protection of persons (Comité de protection des personnes Sud Méditerranée I 17.00608.001744). The findings from this study, whether positive or negative, will be published in peer-reviewed journals and will be presented at national and international conferences. The results will inform future recommendations on the management of RA.Trial registration number NCT03227419 and EudraCT2017-000947-41.